Disrupting shadow in the prothoracic gland induced larval development arrest in the fall armyworm Spodoptera frugiperda - Wu, Mian-Zhi; Fan, Shu-Ting; Zhang, Yuan-Chen; Tan, Jin-Fang; Zhu, Guan-Heng (Frontiers in Physiology, 2024)
IntroductionThe juvenile hormone (JH) and 20-hydroxyecdysone (20E) are the central regulating hormones of insect development. The timing of their secretion usually leads to developmental transitions.MethodsThe developmental transitions were evaluated via the starvation treatment and the expressions of two key metamorphosis inducing factor in Spodoptera frugiperda. Then, the main endocrine organs, including the brain–corpora cardiacum–corpora allatum and prothoracic gland, were sampled from L4-24 h and L6-24 h larvae for the RNA-seq analysis. Additionally, the critical rate-limiting enzyme of 20E synthesis, shadow, was knocked down to mimic the downregulation of 20E synthesis in the late larval instar.ResultsThe critical weight (CW), when JH titer declines for metamorphosis, was determined be approximately L6-24 h in S. frugiperda. However, the expression of the pupal specifier Broad-Complex and the potential “metamorphosis initiation factor” Myoglianin showed a stepwise increase between L4-24 h and L6-24 h, suggesting that the developmental transitions may occur earlier. The RNA-seq analysis revealed that both 20E and JH synthesis enzymes were downregulated at the CW. In addition, strong tendencies in the expression pattern were detected among the lists of transcripts. Further knockdown of shadow induced larval development arrest and subsequent mortality, indicating that disrupting 20E synthesis before the CW is lethal. Besides, JH synthesis enzyme was down-regulated.ConclusionThe downregulation of 20E synthesis enzymes at the CW may represent a carefully regulated event, suggesting a deceleration of larval growth and the initiation of some underlying physiological changes to set the stage for metamorphosis.